Effect of ULVA LACTUCA linn and PADINA TETRASTROMATICA HAUCH concentrate on growth and yield of LABLAB PUPUREUS L. - Priya, R.Vishnu; Flora, G. (Asian Journal of Biological and Life Sciences, 2017)
Apot experiment was conducted to investigate the effect of seaweed concentrate of Ulva lactuca Linn and Padina tetrastromatica HAUCH on the growth and biochemical characteristics of Lablab purpureus L. The growth parameters such as root length, shoot length, no of leaves and no. of th th tendrils were recorded during the period of 30 day and 40 day after treatment. The highest shoot length, root length, no of leaves, no of tendrils were recorded in the L.purpureus treated with P.tetrastromatica concentrate than the control and U.lactuca concentrate treated plants. The seaweeds th enhanced the vitamin-c content, the maximum (1.502 mg/g fw) was recorded in L. purpureus on the 40 day treated with P.tetrastromatica extract. Biochemical constituent in leaves treated with P.tetrastromatica concentrate was enhanced in comparison with U. lactuca concentrate.
Keywords: Antioxidant; FT-IR; Vegetable plant- L. purpureus. L; P. tetrastromatica (HAUCH); Growth parameters; Seaweed Liquid Fertilizer; Marine seaweed U. lactuca (LINN)